Influence of Irradiation on Mechanical Properties of Nickel - Lei Ma; Changsheng Li; Xue Shang; Wangyu Hu (Advances in Materials Science and Engineering)
The influence of irradiation on mechanical properties of nickel is studied using molecular dynamics (MD) simulation. The single crystal nickel is irradiated with the primary knocked-on atom (PKA) energies of 5 keV, 10 keV, 20 keV, and 30 keV at 300 K, and then the tensile test is performed. The simulation results reveal that the yield strain and yield stress of irradiated nickel decrease with the irradiation energy increasing, while the elastic modulus has no obvious change at various irradiation energies. By analyzing the stress-strain curves and the microstructure evolution, it is found that the effect of irradiation accelerates the damage of the internal structure due to the existence of irradiation defects, and high-energy irradiation leads to the instability of the structure in the process of plastic deformation.